Infarction of Ventral Pons Presenting as Millard-Gubler Syndrome - Haseeb Ahmed, Haseeb Ahmed; Mujtaba Haider Bukhari, Mujtaba Haider Bukhari; Murtaza Asghar, Murtaza Asghar (Students’ Supplement of Journal of Rawalpindi Medical College, 2019)
Ventral Pontine Syndrome also called MillardGubler Syndrome is defined as a unilateral lesion of the ventral pons at the level of the facial nerve nucleusthat presents as unilateral facial nerve and abducens nerve palsy with contralateral hemiplegia.1 It has been reported that it is caused by infarction, tumor or tuberculosis. 2-4 This case report describes a patient with ischemic infarction of the left pons presenting as MillardGubler syndrome. Thediagnosis was confirmed by magnetic resonance imaging (MRI). As the condition is not well-known and it may be misdiagnosed especially in patients with current and/or family histories of other neurological diseases such as multiple sclerosis, it becomes imperative that this case must be reported.